Sucrose Esters as Oleogelators in Mono or Binary Structured Oleogels Using Different Oleogelation Routes - Thais Lomonaco Teodoro da Silva; Sabine Danthine (Gels, 2023)
Sucrose esters (SE) have been investigated as structuring agents in oleogels. Due to the low structuration power of SE as single agent, this component has recently been explored in combination with other oleogelators to form multicomponent systems. This study aimed to evaluate binary blends of SEs with different hydrophilic-lipophilic balances (HLBs) with lecithin (LE), monoglycerides (MGs) and hard-fat (HF), according to their physical properties. The following SEs, SP10-HLB2, SP30-HLB6, SP50-HLB11, and SP70-HLB15, were structured using three different routes: “traditional”, “ethanol” and “foam-template”. All binary blends were made using a 10% oleogelator in 1:1 proportion for binary mixtures; they were then evaluated for their microstructure, melting behavior, mechanical properties, polymorphism and oil-binding capacity. SP10 and SP30 did not form well-structure and self-standing oleogels in any combination. Although SP50 showed some potential blends with HF and MG, their combination with SP70 led to even more well-structured oleogels, with a higher hardness (~0.8 N) and viscoelasticity (160 kPa), and 100% oil-binding capacity. This positive result might be attributed to the reinforcement of the H-bond between the foam and the oil by MG and HF.